1999
DOI: 10.1097/00005392-199905000-00026
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Pressure Flow Parameters With Finasteride Is Greater in Men With Large Prostates

Abstract: Finasteride treatment resulted in improvements in urodynamic parameters, which were greater in men with large prostates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
0
5
0
2
Order By: Relevance
“…Many RCTs have demonstrated the clinical efficacy of finasteride in reducing prostate volume and in improving symptom scores and urinary flow rates [46, 49, 86, 87, 88, 89, 90, 91, 92, 93, 94, 95, 96, 97, 98, 99, 100](table 4, 5, 6). Two pivotal phase III trials demonstrated clinical benefit in patients treated with finasteride 5 mg over placebo [91, 94].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many RCTs have demonstrated the clinical efficacy of finasteride in reducing prostate volume and in improving symptom scores and urinary flow rates [46, 49, 86, 87, 88, 89, 90, 91, 92, 93, 94, 95, 96, 97, 98, 99, 100](table 4, 5, 6). Two pivotal phase III trials demonstrated clinical benefit in patients treated with finasteride 5 mg over placebo [91, 94].…”
Section: Resultsmentioning
confidence: 99%
“…Upon analysis, it was discovered that the difference in the magnitude of improvement between finasteride and placebo becomes significant for men with baseline prostate volumes of >40 cm 3 , and that baseline prostate volume was the key predictor of treatment outcomes, with approximately 80% of the variation in the treatment effects noted between studies attributable to differences in mean baseline prostate volume. Furthermore, men with prostates of >40 cm 3 also showed greater improvement in terms of prostate volume and urinary flow in another recent multi–centre international trial of 200 symptomatic men [99]. In the major trial reporting minimal impact of finasteride on QOL and symptom scores described above, the mean prostate volume was only 36 cm 3 [46], and thus these patients do not represent those most expected to benefit from finasteride therapy.…”
Section: Resultsmentioning
confidence: 99%
“…According to the AUA symptom score, this patient has mild symptoms of BPH (mild, 0-7; moderate, [8][9][10][11][12][13][14][15][16][17][18][19]; and severe, 20-35). 10 The AUA symptom index is a reliable and valid method to assist with both diagnosing BPH and monitoring patients' symptoms over time (see Table).…”
Section: Discussionmentioning
confidence: 99%
“…Mediante estudio de presión/flujo, Abrams et al 27 observaron que Finasterida provocaba una disminución significa-…”
Section: Tabla IV (Continuación) Caracterización De Los Estudios Reviunclassified